The Big Book of Girl Stuff - Bart King & Jennifer Kalis
The Big Book of Girl Stuff shares everything a girl needs to know$1 (Bfrom sleepovers to diaries to makeup to boys to shopping, and everything in between! It's the ultimate guide to unlocking the delightful mysteries of being a girl. Dozens of girls, young women, teachers, and mothers collaborated on this book to make it the most comprehensive guide to being a girl that has ever existed! Perfect for pre-teen, 'tween, and teenage girls, The Big book of Girl Stuff shares inspiration, empowerment, and some seriously silly laughs just when girls need it the most! It's filled with information, activities, quotes, and games, as well as lists for favorite books, movies, and music. Smart asides, fascinating facts, an enlightened outlook, and a uniquely feminine perspective make this a must have for every girl. Though it's written for girls from 9 to 14, it will certainly delight moms, aunts, and big sisters everywhere! Find answers to a girl's most important.s